Elastic strain engineering of ferroic oxides. (12th February 2014) - Schlom, Darrell G.; Chen, Long-Qing; Fennie, Craig J.; Gopalan, Venkatraman; Muller, David A.; Pan, Xiaoqing; Ramesh, Ramamoorthy; Uecker, Reinhard
Abstract: Abstract : Using epitaxy and the misfit strain imposed by an underlying substrate, it is possible to elastically strain oxide thin films to percent levels—far beyond where they would crack in bulk. Under such strains, the properties of oxides can be dramatically altered. In this article, we review the use of elastic strain to enhance ferroics, materials containing domains that can be moved through the application of an electric field (ferroelectric), a magnetic field (ferromagnetic), or stress (ferroelastic). We describe examples of transmuting oxides that are neither ferroelectric nor ferromagnetic in their unstrained state into ferroelectrics, ferromagnets, or materials that are both at the same time (multiferroics). Elastic strain can also be used to enhance the properties of known ferroic oxides or to create new tunable microwave dielectrics with performance that rivals that of existing materials. Results show that for thin films of ferroic oxides, elastic strain is a viable alternative to the traditional method of chemical substitution to lower the energy of a desired ground state relative to that of competing ground states to create materials with superior properties.